Investigation of mechanical shock testing of lead-free SAC solder joints in fine pitch BGA package - CHIN, Y; LAM, P; YOW, H; TOU, T (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The lead-free Sn-Ag-Cu (SAC 305/405) solder that replaced the tin-lead eutectic solder tends to be more brittle in nature due to high stiffness and excessive solder interfacial reactions. This leads to higher occurrences of solder joints failure during surface mount assembly and handling operations as a result of PCB bending, shock impact and drop. In this work, mechanical tests simulating the shock impact were conducted on lead-free SAC of different weight percentages. These SAC materials were prepared for use in the solder joints of fine pitch ball grid array (BGA) components which were mounted onto the mother-board. After the mechanical shock tests, strain measurements were performed on the BGA components to gauge the solder joint integrity, which was shown to be related with the formation of intermetallics in the bulk and at the interface of the SAC solder. The ball pull tests were conducted to determine both the bulk and interfacial strength and the solder joint fracture, which was classified as either mode 1, 2 or 3. A correlation was made between the silver (Ag) and copper (Cu) weight percentages with the metallurgical reactions. (C) 2008 Elsevier Ltd. All rights reserved.